Constitutional Rules on Waqf and Fiscal Policy Outcomes - Abdul Ghafar Ismail; Wahyu Ario Pratomo (Faculty of Law, Sriwijaya University, Indonesia, 2021)
Fiscal policy, inter alia, looks at the list of government revenues. The constitutional rules provide guidance on the list of revenues. However, the previous studies find that waqf is not considered as part of government revenues. In this study, we argue that waqf brings in a new list of government revenues. To prove this point, we select a sample of fifty-seven countries under the Organization of Islamic Countries. The constitution of each country is investigated by using content analysis. The study uses a combination of several keywords, namely â€œtax or taxes or fiscal obligations,â€ â€œrevenues or budget or financeâ€ and â€œwaqfâ€ in investigating the rules on revenues and waqf. The findings in this study are classified into five kinds of countries, namely countries that highlight government revenue and waqf in the constitution, countries that claim to recognize sharia law as the basis of the law but the waqf rules in the constitution are missing, countries that mention in their constitution that government revenues are placed under the government system, financial system, and parliament, countries that place waqf is ruled under the public finance matter, and countries that place waqf as the main policy. This finding implies that the constitutional rules lead to the view that waqf is a part of public finance that can be used as a fiscal policy tool and should be included in the state budget plan.